2009
DOI: 10.4012/dmj.28.686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasma treatment on the shear bond strength between fiber-reinforced composite posts and resin composite for core build-up

Abstract: The aim of this study was to evaluate the effects of plasma treatment on adhesion between fiber-reinforced posts and a composite core material. Two types of posts, methacrylate-based (FRC Postec) and epoxy resin-based (DT Light-Post), were treated with oxygen plasma (O2), argon plasma (Ar), nitrogen plasma (N2), or helium mixed with nitrogen plasma (He+N2) using a radio-frequency generator before bonding to a methacrylate-based composite. Pull-out tests were performed using a universal testing machine. Surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
72
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 26 publications
2
72
0
1
Order By: Relevance
“…Therefore a limited chemical bonding between these substrates can be expected. However, with plasma treatment, the surfaces of some polymers can be improved in terms of hydrophilicity by forming oxygen-containing functional groups, such as C=O and -OH [18]. Thereby, the composition of the plasma gas should preferably match the chemical structure of the polymer in order to improve the latter's adhesive properties [19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore a limited chemical bonding between these substrates can be expected. However, with plasma treatment, the surfaces of some polymers can be improved in terms of hydrophilicity by forming oxygen-containing functional groups, such as C=O and -OH [18]. Thereby, the composition of the plasma gas should preferably match the chemical structure of the polymer in order to improve the latter's adhesive properties [19].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen plasma treatment has already been shown to induce amine and imine carbon species as functional groups on polystyrene surfaces [3] displaying terminal nitrogen. Another study hypothesized that thereby induced functional groups on the surfaces of fibre-reinforced composite posts might also contain terminal nitrogen, which then reacts with the functional groups in the composite core build-up materials itself [4] and moreover, that these amine and imine functional groups might remain stable over time as compared to functional oxygen groups. Indeed, nitrogen plasma treatment appeared to increase the tensile-shear bond strength between post and composite and nitrogen functional groups were apparently induced on the surface, which became more stable.…”
Section: Discussionmentioning
confidence: 99%
“…It is biocompatible and exhibits good mechanical properties [2]. It displays a rather low surface energy and high resistance to surface modification by different chemical treatments [3,4] and is therefore stable to nearly all organic and inorganic chemicals. However, it still remains a problem to achieve adequate bond strengths to composite resin materials.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma irradiation does not cause environmental pollution and is a useful method to increase adhesive strength between heat-cured acrylic resin and self-curing acrylic resin [11]. Recent study indicated that plasma treatment appeared to increase the tensile-shear bond strength between post and composite [12]. The bond strength between silicone-based soft liner and fresh denture base has been investigated in previous studies [13,14].…”
mentioning
confidence: 99%